1991
DOI: 10.4315/0362-028x-54.7.492
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Salmonella from High-Moisture Foods by Abbreviated Selective Enrichment

Abstract: Five high-moisture foods were used to evaluate both the effect of a 6 h, rather than the standard 24 h, selective enrichment incubation period, and the efficiency of Rappaport-Vassiliadis (RV) medium relative to the use of selenite cystine (SC) and tetrathionate (TT) broths for the recovery of Salmonella. Cheese and lettuce were artificially inoculated with a pool of two serotypes, whereas the other foods were naturally contaminated. Significantly higher numbers of Salmonella-positive test portions were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…These protocols serve to inhibit microbial competitors while favours Salmonella growth (24,26). However, it has been shown that many of these protocols can affect negatively the sensitivity of the ELISA, increasing the number of false negatives (1). In this study we were able to show that the use of an enrichment protocol with a reduced incubation time does not affect the sensitivity of the ELISA with MAb 424H.…”
Section: Discussionsupporting
confidence: 56%
“…These protocols serve to inhibit microbial competitors while favours Salmonella growth (24,26). However, it has been shown that many of these protocols can affect negatively the sensitivity of the ELISA, increasing the number of false negatives (1). In this study we were able to show that the use of an enrichment protocol with a reduced incubation time does not affect the sensitivity of the ELISA with MAb 424H.…”
Section: Discussionsupporting
confidence: 56%
“…As confirmed the results of our study, use of SC broth results in a lower diagnostic sensitivity than the use of MSRV plates and TTN broth. 2,8 In our study, comparison of the use of TTN broth with that of MSRV plates and SC broth indicates that the use of TTN broth and MSRV plates results in significantly different diagnostic sensitivities for Salmonella organisms (0.57 and 0.64, respectively). However, Proteus spp can be suppressed by novobiocin.…”
Section: Discussionmentioning
confidence: 64%
“…

S almonella organisms are major food-borne pathogens, and bacteriologic cultures of fecal samples from subclinically infected herds provide the established protocol for detection and isolation of Salmonella organisms. 2 The purpose of the study presented here was to compare the diagnostic sensitivity and detection limit of 3 alternative culture methods or protocols with the established ISO protocols.

Materials and MethodsSample collection-From pens of herds of naturally infected pigs, fecal samples were collected into 50-ml plastic jars. This has increased the interest in rapid and cost-effective culture methods.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suggested protocols also vary with the substrate: Kafel (l981) suggested the use of anaerobic lactose broth, followed by selection in tetrathionate brilliant green broth and plating on brilliant green agar, in the analysis of fish meal. Allen et al (1991) reported that the sensitivity of Rappaport Vassiliadis medium depended on the substrate in the detection of Salmonella spp. in high moisture foods, compared with tetrathionate or selenite cystine broth.…”
Section: Detection Methodsmentioning
confidence: 99%